2020
DOI: 10.3390/en13040871
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the High-frequency Pressure Oscillation Characteristics of a Combustion Process in a DI Diesel Engine

Abstract: It is difficult to decompose the in-cylinder pressure of combustion of the direct injection (DI) diesel engine, a transient process associated with complicated oscillation components, because of its steep property. An adaptive cyclic average method based on time varying filter based empirical mode decomposition (TVF-EMD) is proposed to decompose the in-cylinder pressure signal, and the cyclic number is determined adaptively with protruding ratio of high-frequency oscillation. The proposed method is used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Katrasnik et al (Katrasnik et al, 2006) developed a new criterion for the determination of the start of combustion (SOC) from the diesel engine in-cylinder pressure diagram based on the maximum of the thirdorder derivative of the cylinder pressure with respect to the crank angle. Zheng et al (Zheng et al, 2020) found that the energy of high-frequency oscillation reached peak at medium-high speed and increased with engine load and rail pressure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Katrasnik et al (Katrasnik et al, 2006) developed a new criterion for the determination of the start of combustion (SOC) from the diesel engine in-cylinder pressure diagram based on the maximum of the thirdorder derivative of the cylinder pressure with respect to the crank angle. Zheng et al (Zheng et al, 2020) found that the energy of high-frequency oscillation reached peak at medium-high speed and increased with engine load and rail pressure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notwithstanding, SPE is often used as membrane in proton exchange membrane fuel cell (PEMFC) application. PEMFC offers high energy efficiency (>80%), benign environment and reduced noise pollution comparing to diesel engines [ 3 ]. Other applications of polymer electrolyte based on ionic liquid can be found in solar-driven steam [ 4 ] and supercapacitor [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the applications of EMD are also restricted due to the existence of the end effect and mode mixing [2]. Zheng et al [3] proposed an adaptive cyclic average method based on the TVF-EMD to extract high-frequency oscillation characteristics, from which the cyclic number can be adaptively determined. The local mean decomposition (LMD), a development of the EMD, decomposes the signal into a series of product functions [4,5].…”
Section: Introductionmentioning
confidence: 99%